A unified Marxist approach to accumulation and crisis in capitalist economies - Deepankar Basu (University of Massachusetts, Department of Economics, 2017)
An economic crisis in capitalism is a deep and prolonged interruption of the economy-wide circuit of capital. Crises emerge from within the logic of capitalism's operation, and are manifestations of the inherently contradictory process of capital accumulation. The Marxist tradition conceptualizes two types of crisis tendencies in capitalism: a crisis of deficient surplus value and a crisis of excess surplus value. Two mechanisms that become important in crises of deficient surplus value are the rising organic composition of capital and the profit squeeze; two mechanisms that are salient in crisis of excess surplus value are problems of insufficient aggregate demand and increased financial fragility. This paper offers a synthetic and synoptic account of the Marxist literature on capitalist economic crises.
Keywords: B24; B51; 330; capitalism; crisis; rising organic composition; profit squeeze; underconsumption; financial fragility